Endogenous local labour markets, regional aggregation and agglomeration economies - J. Meekes; Wolter H.J. Hassink (Utrecht University, Utrecht University School of Economics, Tjalling C. Koopmans Research Institute, 2018)
In this paper, we examine the structure of workers' local labour market (LLM) and its economic consequences. We endogenise workers' LLM to commuting outcomes and worker characteristics. The descriptive results indicate that both male workers and high-educated workers especially are characterised by large LLMs. The empirical results show that the urban wage premium (UWP), explained by the returns to agglomeration in wages, increases by a magnitude of two to three in the level of regional aggregation. We also focus on subgroup differentials in the returns to agglom-eration economies. High-educated workers experience a higher UWP than low-educated workers, but we find no systematic difference between the UWP of men and women when holding the re-gional aggregation level constant. In addition, we examine the returns to agglomeration in wages and employment for workers who experienced job displacement. We show that at a relatively high level of regional aggregation, displaced workers in dense LLMs, compared to displaced workers in more sparse LLMs, experience modest losses in wages and comparable losses in employment.
Keywords: 330; Local labour markets; Urban wage premium; Employment; Commuting; Regional aggregation; Tra